The Duncan Method of Partial Pillar Extraction at Tasman Mine (8325db0b-edfd-48b5-8c88-7ef0db101af9) - Kent D. Mctyer (International Conference on Ground Control in Mining, 2011)
Mining commenced at Tasman Mine in late 2006. The current method of mining is bord and pillar using continuous minerbolters and shuttle cars for first workings and secondary extraction using mobile roof supports. The two stage process was chosen to accommodate irregularly shaped coal deposits, allowing adjustments to be made to extraction ratios for better management of subsidence and to maximize the efficiency of the operation. Following the completion of the first three full/partial extraction panels, the mining method was changed due to variable caving. Another partial extraction method, referred to as the Duncan Method was adopted; it involves stripping the developed square pillars on four-sides on retreat to leave a load-bearing remnant coal pillar. The system of partial extraction has been successful in meeting safety, productivity, and subsidence targets.